Hubungan Conformity dengan Motivasi Belajar Siswa Kelas X SMKN 2 Kota Solok - Siska Febriyani; Agus Firman; Wahyu Tri Prastyo; Zamzami Zamzami; Wiskarni Wiskarni (PAKAR Pendidikan, 2022)
Education is the main thing in life. Every human being has the right to obtain education as development and progress in itself. Education is always associated with learning and directly proportional to study habits. The success of the learning process depends on students' motivation and enthusiasm for learning. Student motivation is also influenced by conformism. In adolescence, conformity is very influential on consideration in making decisions. Furthermore, adolescence is an unstable phase and is very sensitive to conformity. This study aims to analyze the relationship between compliance and learning motivation of students in class X of SMKN 2 Kota Solok. The population in this study was Class X, Department of Light Vehicle Engineering, SMKN 2 Kota Solok, for the 2020/2021 academic year, there were 120 students. The sample for this study consisted of 48 students from SMKN 2 Kota Solok. The sampling technique in this study used a random sampling technique. The results of this study indicate the value of rcount > rtable which indicates the validity and the Cronbach alpha > 0.6 which indicates the reliability of the research data. After analyzing the correlation test, it was found that the high level of compliance in class X resulted in the inhibition of students' motivation to learn. Students who perform well tend to be noticed by their peers and have higher motivation than students who perform well and tend to be ostracized by their peers.